Effects of a Mindfulness Intervention Among Arab Teachers Are Mediated by Decentering: A Pilot Study - Berkovich-Ohana, Aviva; Lavy, Shiri; Shanboor, Kholoud (Frontiers in Psychology, 2020)
While mindfulness-based interventions (MBIs) in education are widely spreading in the world, examination of mindfulness effects in Arab schools is still scarce. This pilot study aimed to fill this gap, by examining the effects of an MBI among Arab teachers in Israel. This examination was conducted within the framework of the mindful self in school relationships (MSSR) model, which suggests that the positive effects of MBI on teachers' emotion regulation are mediated by decentering. The participants (N =39) were teachers from two Arab elementary schools in Israel, who underwent an MBI course (the MBI condition; N=20) and another cognitive intervention (the control condition; N=19). In a pre-post design, participants completed mindfulness, decentering, emotion regulation, and stress questionnaires. We hypothesized that: (1) only in the MBI group, teachers’ mindfulness, decentering, and emotional regulation will increase, and stress will decrease; (2) changes in teachers’ decentering would mediate the associations of changes in teachers’ mindfulness with changes in their emotion regulation. ANOVA analyses showed that only in the MBI condition, teachers showed an increase in three mindfulness subscales (acting-with-awareness, non-reactivity, and observance), in decentering, and in adaptive emotion regulation (reappraisal), and a decrease in stress. Furthermore, changes from pre-intervention to post-intervention in teachers’ decentering mediated the associations of their pre-post changes in mindfulness with changes in emotion regulation. This study provides initial support to the feasibility and efficacy of MBI among Israeli Arab teachers, and suggests decentering as a potential mediator of its effects, in initial support of the MSSR model.